1986
DOI: 10.1152/ajpcell.1986.250.3.c486
|View full text |Cite
|
Sign up to set email alerts
|

Ba2+ inhibition of VIP- and A23187-stimulated Cl- secretion by T84 cell monolayers

Abstract: Addition of either 10(-8) M vasoactive intestinal polypeptide (VIP) or 10(-6) M A23187 to T84 cell monolayers, grown on permeable supports and mounted in Ussing chambers, stimulated net Cl- secretion. The effect of 10(-6) M A23187 on Cl- flux was consistently smaller than that observed with 10(-8) M VIP. In both cases the increase in net Cl- secretion accounted for the entire change in the observed short-circuit current (Isc). Since Cl- enters the cells through a basolaterally localized Na+-K+-Cl(-)-cotranspor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(68 citation statements)
references
References 27 publications
7
61
0
Order By: Relevance
“…There were no effects of forskolin on basolateral PK. It has been previously concluded that cAMP either activates (42) or has no effect (33) ( Fig. 9 A) and also toward the basolateral side (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…There were no effects of forskolin on basolateral PK. It has been previously concluded that cAMP either activates (42) or has no effect (33) ( Fig. 9 A) and also toward the basolateral side (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Forskolin has been shown to inhibit amiloride-sensitive Na¤ transport in rat colon (Ecke et al 1996) and further experiments are required to elucidate the exact effect of cAMP on Na¤ transport in intact human colonic epithelium. Apical chloride transport must be coupled to basolateral potassium transport if a favourable gradient for chloride secretion is to be maintained (Mandel et al 1986). There are believed to be two signal transduction pathways involved in human colonic secretion (Weyer et al 1985;Dharmsathaphorn & Pandol, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Growth and maintenance of T84 cells, transepithelial electrolyte transport studies, and measurement of cAMP were performed as described earlier (14)(15)(16). Measurement of cGMP utilized a similar procedure to that described for cAMP except that a cGMP standard and cGMP antiserum were used instead of the cAMP standard and cAMP antiserum (22).…”
Section: Methodsmentioning
confidence: 99%
“…It is, therefore, difficult to define the mechanisms of bile acid induced electrolyte and water secretion at the cellular level based on in vivo studies or in vitro studies using isolated intestine. Recently, our laboratory has utilized a well-differentiated colonic epithelial cell line as a model system to study the mechanisms of secretagogueinduced Cl-secretion (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The uniformity of this model epithelium allows a less ambiguous characterization ofthe secondary messengers involved in the Cl-secretory process.…”
Section: Introductionmentioning
confidence: 99%